Kajian Faktor Lingkungan Fisik Pinus merkusii Jungh et de Vries Ras Kerinci di Resort KSDA Bukit Tapan, Kawasan Taman Nasional Kerinci Seblat, Jambi - Istomo .; Cecep Kusmana; Syafda Roswandi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2000)
Species of Pinus merkusii Jungh et de Vries of Kerinci is a unique variety, because this species grows naturally in southernKerinci Mountain. Objectives of this research were to identify growth distribution of P. merkusii Kerinci variety based on field condition and to determine important physically factors for growth of P. merkusii Kerinci variety. This research was conducted in montane rain forest of Bukit Tapan, Kerinci Seblat national park region for two months (April-May 1996). This research used multiply plot sampling with rectangular form (20 m x 20 m) in 24 the research sampling plots. Soil samples were taken from each plot for soil c h d s t i c analysis. Data was analyzed by vegetation analysis, ordination, and multiple regression linear by stepwise procedure to identify mostinfluence's physical factors. Research was found 47 trees species classified within 39 genus and 25 family. The 24 permanent plots wen dominated by P. merkusii (IVI = 115.33%). Number of P. merkusii in each permanent plot among 1-13 trees. Range of basal area of pines between 0.66 m2ha and 39.08 m21ha whereas non-pines among 4.06 m2ha and 13.88 m h a . The result of research showed that P.merkusii Kerinci variety grow well in Litosol soil, with sandy clay texture, with proportion of sand : dust : clay are 14 : 5 : 1 or I5 : 4 : 1, 53.21-56.48% of porosity and 1.14-1.24 g/cc of bulk density.